PENERAPAN PUZZLE MODIFIKASI UNTUK MENINGKATKAN KEMAMPUAN IDENTIFIKASI RUANG - Eka Poppi Hutami; Mayawati Mayawati (Jurnal Panrita, 2022)
The problem of this research regarding the ability to identify space in students has not emerged. For this reason, the research aims to improve spatial identification abilities through the application of a modified puzzle in group A of Bina Bakti Cinnong Kindergarten, Sibulue District, Bone Regency. This classroom action research refers to the Kemmis and Taggart action research model modified by Martini Jamaris which begins with an initial assessment, plan, action, observation, reflection, then re-plan, action, observation, reflection, final assessment. The results of the first cycle reached an average of 13.80 with a three-star (***) award, which means that the average child is able to be independent and is starting to be consistent, the result is with a presentation of 69%, which means that it is still below 71%, which is not yet completed. The results of the second cycle reached an average of 16.40 with a four-star award (****), which means that on average children do it independently and can help their friends who have not finished carrying out learning activities, the results are with a presentation of 82%, which means they are still under below 71%, that is already completed. The results of the increase from cycle I to cycle II were 14 with a percentage of 60%. The results of the study show that the application of puzzles designed with modified game pattern designs can increase.